PERCEPTIONS OF STUDENTS OF THE FACULTY OF AGRICULTURE ON THE SOCIAL STATUS AND CAREER PROSPECTS IN THE AGRICULTURAL SECTOR - Yasinta Zulaikha; Edhi Martono; Fathul Himam (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The phenomenon of the declining interest of young workers working in the agricultural sector has consequences for the sustainability of the agricultural sector going forward. In the future, the burden on the agriculture sector will be heavier with the inc reasing population and increasing food demand. The reasons for the decline in the interest of young workers works at agricultural sector are mainly caused by the image of the agricultural sector which is less prestigious and can not provide adequate rewards. The crisis of young farmers in the agricultural sector and the predominance of older farmers has consequences for the agriculture sector development, particularly on agricultural productivity, market competitiveness, ruraleconomic capacity, and further it will threaten food security and agricultural sector sustainability. The objective of the research is to know the effect of social to career prospects on agricultural career empirically. The research involves 110 respondents with a questionnaire as a research instrument. The type of research in this study is survey research, the type of research which the way to collect data obtained or collected from the sample or population under study. Testing is done with a regression test to determine the effect of social status on career prospects in agriculture. The results of this study indicate that social status has an influence on perceptions of career prospects in the agricultural sector.